Sumatriptan Induced Takotsubo Cardiomyopathy; the Headache of the Heart: A Case Report - Mohan, Jay; Parekh, Akarsh; DeYoung, Michael (Frontiers in Cardiovascular Medicine, 2019)
Takotsubo Cardiomyopathy (TCM) is an increasing recognized form of acute reversible left ventricular systolic dysfunction not related to obstructive coronary disease. The exact physiology of this disorder is not yet known, however multiple agents have been hypothesized to have a link to this condition. Most commonly, TCM has been hypothesized as being triggered by a catecholamine surge after an inciting event. New evidence now suggests certain medications as a link to the disease. We describe a unique case of TCM in a woman after taking Treximet (naproxen and sumatriptan) as abortive therapy for a migraine.